Impact of New Economic Policy on Agriculture Development With special Reference to BIHAR - Jha, DR. T.N. (JOURNAL OF BUSINESS MANAGEMENT & QUALITY ASSURANCE, 2022)
Irrigation and The agriculture sector has been playing an important role in the economic development of Uttar Pradesh. The agriculture at the time of independence was very insignificant. It was suffering from problems of illiteracy, poverty, starvation, low productivity, poor technology, and lack of capital, lack of agricultural machinery, transportation, power, marketing, inadequate irrigation facilities and skewed distribution of land holdings. The government adopted high yielding varieties technology or green revolution for the development of agricultural sector through increase the production and ensure job security for the poor farmers and increase capital in agriculture. As results, the growth of agriculture sector increased and the country achieved self-reliance in food security. But the growth of population is geometric and agricultural production is arithmetic. There was food security problem. The agriculture sector has been facing the problems of low-level capital, poor technology, low productivity, disguised unemployment, population pressure on land and unequal distribution of land holdings. During the 1990s, the new economic policy brought tremendous changes in the agriculture sector with increasing investment, arrival of multinational companies, opening the door of public sector for the private sector and financial sector reforms. The new agricultural policy allowed agriculture sector to global agriculture business and had implications for the rural population, food security, employment and poverty at the state and national level. Hence, an attempt is made to analyse the impact of new economic policy on agricultural development with special reference to the state of BIHAR in terms of agricultural growth, income, production, productivity, and technology. This study based on secondary data collected from various reports, planning commission and census and others. The land use pattern is changing and diversification and commercialisation of crops are increasing in the state of Uttar Pradesh. Keywords: Agriculture GDP, Productivity, New Economic Policy, Agriculture Development Commercialization, Technology